2001
DOI: 10.1046/j.1365-2141.2001.03204.x
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and biological effects of thalidomide in patients with myelodysplastic syndromes

Abstract: Summary. Thirty patients with myelodysplastic syndromes (MDS) were treated with thalidomide at 100 mg/d p.o., increased as tolerated to 400 mg/d for 12 weeks. Levels of apoptosis, macrophage number, microvessel density (MVD), tumour necrosis factor alpha (TNF-a), transforming growth factor beta (TGF-b), interleukin 6 (IL-6), vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (bFGF) were determined in the serum, bone marrow (BM) plasma and BM biopsies before and after therapy. Prethera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(56 citation statements)
references
References 47 publications
(50 reference statements)
6
49
0
1
Order By: Relevance
“…Three of the patients had responding myeloma and, in retrospect, a del(5q) chromosome abnormality, a characteristic cytogenetic aberration in myeloma patients subsequent to prolonged standard-dose melphalan treatment (Govindarajan et al, 1996;Amiel et al, 1999). Despite published data indicating the efficacy of thalidomide in subsets of patients with MDS or AML (Zorat et al, 2001;Steins et al, 2002;Strupp et al, 2002), our observations suggest that thalidomide, at least in combination with dexamethasone and cyclophosphamide, does not control and may even adversely affect concurrent MDS/sAML. Its use should be considered with caution in patients with suspicious cytogenetic abnormalities.…”
Section: Discussionmentioning
confidence: 56%
“…Three of the patients had responding myeloma and, in retrospect, a del(5q) chromosome abnormality, a characteristic cytogenetic aberration in myeloma patients subsequent to prolonged standard-dose melphalan treatment (Govindarajan et al, 1996;Amiel et al, 1999). Despite published data indicating the efficacy of thalidomide in subsets of patients with MDS or AML (Zorat et al, 2001;Steins et al, 2002;Strupp et al, 2002), our observations suggest that thalidomide, at least in combination with dexamethasone and cyclophosphamide, does not control and may even adversely affect concurrent MDS/sAML. Its use should be considered with caution in patients with suspicious cytogenetic abnormalities.…”
Section: Discussionmentioning
confidence: 56%
“…A higher expression of TNF receptors and TNF mRNA have also been reported in diseased bone marrows, 6,7 with the source of cytokine production localized to bone marrow macrophages. 8 High levels of Transforming growth factor beta (TGFb), another myelosuppressive cytokine, have been detected in diseased bone marrow plasma 4 and have been observed on the surface of hematopoietic progenitors. 2 Similarly, interferon g has been implicated strongly in another bone marrow failure syndrome, aplastic anemia, and studies have shown that MDS bone marrow mononuclear cells have higher IFNg mRNA transcripts when compared to healthy controls.…”
Section: Myelodysplasia Is a Preleukemic Syndrome Characterized By Inmentioning
confidence: 99%
“…Tumor necrosis factor alpha (TNFa) is the classic pro-apoptotic cytokine that has been implicated in the accelerated progenitor apoptosis in MDS. 2,3 This is based on the presence of high plasma concentrations of TNFa in the peripheral blood 4 and bone marrow 5 of MDS patients, and the improvement in progenitor recovery with in vitro cytokine neutralization. A higher expression of TNF receptors and TNF mRNA have also been reported in diseased bone marrows, 6,7 with the source of cytokine production localized to bone marrow macrophages.…”
Section: Myelodysplasia Is a Preleukemic Syndrome Characterized By Inmentioning
confidence: 99%
“…In addition to increased TNF-alpha and INF-gamma in the marrow of MDS patients, varying levels of angiogenic factors including VEGF (vascular endothelial growth factor), bFGF (fibroblast growth factor), angiogenin, HGF (hepatic growth factor), EGF (epidermal growth factor), and TGF-beta (transforming growth factor) have been noted in the plasma of MDS patients. These findings, coupled with direct evidence of increased microvascular density (MVD) on marrow biopsies, support the development of early blood vessels in MDS [120][121][122][123]. Both plasma VEGF levels and increased MVD correlate with advanced MDS FAB class [124][125][126] and imply that increased VEGF may drive increased MVD eventually stimulating MDS progression to AML.…”
Section: Altered Bone Marrow Microenvironment: Apoptosis Cytokines Amentioning
confidence: 61%